Stress Physiology and Behavior Problems - Chen, Ruiyun (2016)
Understanding childhood externalizing problems is informative in designing interventions and reducing crime in adulthood because childhood aggression is one of the best predictors for later antisocial behavior. Childhood externalizing problems are typically studied with internalizing problems (e.g., anxiety) given their consistent correlation and seemingly opposite behavior manifestations. This dissertation examined both spectrums of behavior problems to advance our etiological understanding. Adversity and stress have been a focus in criminology research but few studies have incorporated stress physiology, the biological underpinning of how individuals deal with adversity. This dissertation comprised three papers testing the linkage of stress physiology to behavior problems. I examined how the two components of the stress system, namely the hypothalamic-pituitary-adrenal (HPA) axis and the autonomic nervous system (ANS), interact with each other, and together interact with harsh discipline in influencing externalizing and internalizing problems. Data were drawn from a community sample of 11-12 year old children (N = 446). Saliva samples were collected in the initial assessment and later assayed for cortisol (HPA) and salivary alpha-amylase (sAA; ANS). Participants and their caregivers completed questionnaires for child behavior problems initially, 3, 6, and 12 months later. Paper 1 revealed that cortisol was negatively associated with externalizing and internalizing problems but only at low levels of sAA. Paper 2 built on Paper 1 by including harsh discipline as an environmental factor and testing how the combined effect of cortisol and sAA contributed to our understanding of the heterogeneous effect of harsh discipline on behavior problems. Results showed that asymmetry in cortisol and sAA may indicate biological susceptibility to the effect of harsh discipline to develop both externalizing and internalizing problems among boys. Given the similar stress physiological patterns shown in Paper 1 and 2 for externalizing and internalizing problems, Paper 3 further explored and found that the interplay of cortisol and sAA differentiated co-occurrence of behavior problems from other developmental trajectories of behavior problems over a year. Together these findings underscore the significance of stress physiology in behavior problems. Theoretical implications in relation to differential susceptibility hypothesis and practical implications for treatment evaluation and research are discussed